Purulent Pericarditis in an Immunocompetent Young Child - Şeyma Şebnem Ön; Ahmet Bozkurt; Fırat Ergin; Burcugül Karasulu Beci; Kübra Cebeci; Pınar Yazıcı Özkaya; Bülent Karapınar; Eser Doğan; Osman Nuri Tuncer; Zülal Ülger (Galenos Yayinevi, 2024)
Purulent pericarditis in children is a life-threatening condition causing cardiac tamponade and disrupting the hemodynamic status of the patient. It has been associated with high mortality if treatment is delayed. Furthermore, purulent pericarditis may lead to constrictive pericarditis in the long term if not fully treated. Acute purulent pericarditis should be seriously considered in every septic child presenting with signs of right heart decompensation. Echocardiography is important for diagnosis. Diagnostic pericardiocentesis should be performed. Recent experience shows that excellent results can be obtained when adequate surgical drainage and antibiotic therapy are combined. We report a case of purulent bacterial pericarditis caused by methicillin-resistant Staphylococcus aureus in an immunocompetent young child presenting with sepsis. The patient was successfully treated with a combined medical and early surgical approach.